(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
We show in this article the use of the norm function to get a new lower bound of Riemann-Zeta function where. This subject has been studied deeply by Hilberdink [HIL, 12]). Getting a bound for the Riemann-Zeta function in the critical strip is more challenging for many reasons related to the behavior of the Riemann-Zeta function in that strip. In the other words, the aim of this article is to prove that has a strict lower bound when the real part is very closed to the line 1. We state this in the main theorem of this paper.